Microbiological and functional outcomes after open extremity fractures sustained overseas: The experience of a UK level I trauma centre. (March 2018) - Ardehali, B.; Geoghegan, L.; Khajuria, A.; Reissis, D.; Lawton, G.; Jain, A.; Simmons, J.; Naique, S.; Bhattacharya, R.; Pearse, M.; Nathwani, D.; Hettiaratchy, S.
Abstract: Background: Open extremity fractures carry a high risk of limb loss and poor functional outcomes. Transfer of extremity trauma patients from developing countries and areas of conflict adds further layers of complexity due to challenges in the delivery of adequate care. The combination of extensive injuries, transfer delays and complex microbiology presents unique challenges. Methods: A retrospective review was conducted to analyse the surgical and microbiological themes of patients with open extremity fractures transferred from overseas to our institution (Imperial College NHS Trust) between January 2011 and January 2016. Results: Twenty civilian patients with 21 open extremity fractures were referred to our unit from 11 different countries. All patients had poly-microbial wound contamination on initial surveillance cultures. Five patients (25%) underwent amputation depending on the extent of osseous injury; positive surveillance cultures did not preclude limb reconstruction, with seven patients undergoing complex reconstruction and eight undergoing simple reconstruction to achievewound coverage. Hundred percent of patients demonstrated infection-free fracture union on discharge. Conclusion: Patients with open extremity fractures transferred from overseas present the unique challenge of poly-microbial infection in addition to extensive traumatic wounds. Favourable outcomes can be achieved despite positive microbiological findings on tissue culture with adequate antimicrobial therapy. The decision to salvage the limb and the complexity of reconstruction used should be based on the chance of achieving meaningful functional recovery, mainly determined by the extent of bony injury. The complexity of reconstruction was based on the predicted long-term functionality of the salvaged limb.